Chapter 24: Celery Production in Florida: HS723/CV121, 12/2005 - Hochmuth, George J.; Maynard, Donald N.; Vavrina, Charles S.; Stall, William M.; Raid, Richard N.; Webb, Susan E. (EDIS, 2019)
This document is HS723, Horticultural Sciences Department, UF/IFAS Extension. Published December 2005.